DGEM-Leitlinie Enterale Ernährung: Hepatologie - Plauth, Mathias; Ferenci, P.; Holm, Eggert; Dahl, S. vom; Kondrup, J.; Müller, M. J.; Nolte, W. (Aktuelle Ernährungsmedizin. Supplement, 2003)
Thieme E-Books & E-Journals
Gesehen am 30.03.2022